Hydrogen Bonding of Carboxylic Acids in Aqueous Solutions—UV Spectroscopy, Viscosity, and Molecular Simulation of Acetic Acid - Ruderman, Graciela (1998)
The UV spectra of aqueous acetic acid solutions up to 2M were investigated. At these wavelengths, the carboxylic acids exhibit an absorption peak, attributed to the C=O group, which shifts when hydrogen bonds are formed.. The measured spectra were best fitted to several bands, either of Gaussian or Lorentzian shape, which can be explained as several types of structural units formed by hydrogen bonds established between acetic acid and water molecules and between acetic acid molecules themselves. Molecular dynamics simulation of these mixtures was also performed, confirming the occurrence of several types of hydrogen bonds and showing the presence of dimers at higher concentrations. The viscosity and density of these solutions were also measured at different concentrations and temperatures. These results give a more complete picture of the hydrogen bond network of the system.